Autonomia e subordinação das universidades : uma investigação dos limites da autonomia universitária - Velten, Andréia Chiabai (2018)
The autarchies, entities belonging to the indirect public administration, are subject to a legal system that distinguishes them from other bodies, enjoying a certain degree of administrative autonomy. Federal universities, as autarchic entities that they are, have this prerogative, but in a much more amplified way, enjoying didactic-scientific, administrative autonomy and financial and patrimonial management, by virtue of article 207 of the Constitution of the Federative Republic of Brazil of 1988, a peculiarity that is intrinsically linked to the very foundation of existence of universities, which presupposes a freedom of thought on which there should be no reservations. On the other hand, the universities are subject to the supervision of some control bodies, as well as some directives issued by the direct public administration, generating a relation of simultaneous dependence and independence that, in addition to confusing the limits of autonomy, often , ends up curtailing your exercise. In this context, the purpose of this study is to investigate the duality that exists between university autonomy and the oversight of control bodies, having as object of study the recommendations issued by the Federal Comptroller General's Office in its audit reports held at the Federal University of Espírito Santo, issued in the last five years. From these reports, the controversial points were extracted, that is, those in which there is divergence of understanding between the University and the control agency, which may indicate that the intervention of the latter exceeds the limits of university autonomy. Subsequently, each of these ocurrences was analyzed, from a jurisprudential perspective, in order to find possible solutions to dissent. Also from the jurisprudential research, it was possible to delimit the subjects of autonomous competence on the part of the universities, in order to elaborate the proposal of interpretation of article 207 of the Magna Carta, technical product of this writing.